The effect of problem-based learning using VARK approach on biology students’ creative thinking skills - Siti Annisaa'ul Kariimah; Herawati Susilo; Utami Sri Hastuti; Balqis Balqis; Wa Ode Nurhawa (Master Program of Biology Education, Universitas Lambung Mangkurat, 2022)
Learning that does not enable creative thinking skills does not facilitate student learning styles. This study aims to determine the effect of the PBL learning model with the VARK approach on the creative thinking skills of Biology students. This research uses quasi-experiment. The research subject was the 58 third-semester of Bachelor’s Degree students in the Department of Biology who took the Plant Physiology course. Data analysis used a single ANCOVA. The results showed that the PBL models with the VARK approach to creative thinking skills were 0.000, which means less than 0.05. These results prove that the research hypothesis is accepted, which means that the application of the learning model has a significant effect on students' creative thinking skills. The results of the 5% on LSD further test for the difference in the results of the two classes were 86.551 for the experimental class using the PBL model with the VARK approach, and 77.828 for the control class using the PBL models without the VARK approach. These results indicate that creative thinking skills using the PBL with the VARK approach have a higher effect than the PBL model without the VARK approach. However, the PBL models with the VARK approach effect increasing the creative thinking skills.AbstrakPembelajaran yang kurang memberdayakan keterampilan berpikir kreatif tidak memfasilitasi gaya belajar mahasiswa. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Problem-based Learning (PBL) dengan pendekatan VARK terhadap keterampilan berpikir kreatif mahasiswa biologi. Metode penelitian ini kuasi eksperimen. Analisis data menggunakan anakova tunggal. Hasil penelitian menunjukkan model pembelajaran PBL dengan pendekatan VARK terhadap keterampilan berpikir kreatif sebesar 0,000 artinya lebih kecil dari 0,05. Ini membuktikan bahwa hipotesis penelitian diterima, artinya penerapan model pembelajaran berpengaruh signifikan terhadap keterampilan berpikir kreatif mahasiswa. Hasil uji lanjut BNT 5% terhadap perbedaan hasil kedua kelas yakni 86.551 untuk kelas eksperimen dengan penerapan model PBL dengan pendekatan VARK, sedangkan 77,828 untuk kelas kontrol dengan penerapan model PBL tanpa pendekatan VARK. Hasil tersebut menunjukkan bahwa keterampilan berpikir kreatif yang menggunakan PBL dengan pendekatan VARK memberikan pengaruh lebih tinggi dibandingkan dengan model PBL tanpa pendekatan VARK. Untuk itu model pembelajaran PBL dengan pendekatan VARK berpengaruh terhadap peningkatan keterampilan berpikir kreatif.